2022
DOI: 10.1186/s12864-022-09044-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of proteomic and metabolomic characterization in atrial fibrillation-induced heart failure

Abstract: Background The exact mechanism of atrial fibrillation (AF)-induced heart failure (HF) remains unclear. Proteomics and metabolomics were integrated to in this study, as to describe AF patients’ dysregulated proteins and metabolites, comparing patients without HF to patients with HF. Methods Plasma samples of 20 AF patients without HF and another 20 with HF were analyzed by multi-omics platforms. Proteomics was performed with data independent acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…In recent times, proteomics and metabolomics have emerged as innovative tools not only for identifying new risk factors but also for elucidating the underlying mechanisms of cardiovascular disease [ 9 ]. Previous studies have revealed aberrant alterations in numerous proteins and metabolites among patients with HFpE [ 19 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent times, proteomics and metabolomics have emerged as innovative tools not only for identifying new risk factors but also for elucidating the underlying mechanisms of cardiovascular disease [ 9 ]. Previous studies have revealed aberrant alterations in numerous proteins and metabolites among patients with HFpE [ 19 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were introduced into a mass spectrometer (Q Exactiv HF-X; Thermo Fisher, Germany) linked to a chromatography platform (EASY-nL 1200 UHPLC system; Thermo Fisher, Germany) with DIA mode selected for data collection. Differentially expressed proteins (DEPs) of significant interest were identified based on a fold-change of ≥ 1.5 or ≤ 0.67 and a t-test p -value of < 0.05 [ 9 ]. Subsequent mapping of DEPs and pathway analysis was facilitated utilizing the KEGG pathway database.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some identified proteins were shared among multiple targeted proteomic studies, which improved the validity of those findings and would be a strength in any other omics findings. 66,[68][69][70] Zhang et al 68 identified and replicated 64 proteins associated with HFrEF hospitalization or cardiovascular death. The significantly associated proteins included a novel protein association, SVEP1 (Sushi, von Willebrand factor type A, EGF and pentraxin domain containing 1), an extracellular matrix protein expressed in vascular smooth muscle that promotes inflammation and atherosclerosis.…”
Section: Proteomicsmentioning
confidence: 99%